Examining the Moral Threshold From the Perspective of Shahīd Moṭahharī with Emphasis on the Reality of Ethics - Ḥusayn Aḥmadī (آموزه‌‌های فلسفه اسلامي)
The moral threshold is regarded as the limit of true happiness. The aim of this research is to conclude this threshold from the statements of Shahīd Moṭahharī, considering the nature of moral reality through a descriptive-analytical method. He perceives the nature of moral reality as religious and based on conscious worship, which cannot exist without belief in monotheism, that is, the moral threshold. It seems that Shahīd Moṭahharī’s expression in proving the nature of moral reality, which embodies religious ethics, requires a corrective and supplementary explanation regarding its foundations and implications. In this way, according to the special characteristics of human beings, the truth of morality should be considered for rational human beings. Based on the pursuit of perfection, humans place nearness (Arabic: قُرْب) to absolute perfection as the object of their reasoning, discovering their need in understanding their relationship with the Absolute Perfection. Consequently, in light of this awareness, they engage in behavior that corresponds to that need, which is the expression of that need and gratitude towards the Giver of it, what Shahīd Moṭahharī refers to as conscious worship.